L’historiographie des actes de la pratique : l’écriture de la conquête normande dans les actes de Sicile et de Calabre du milieu du XIe siècle au début du XIIIe siècle - Annick Peters-Custot (Tabularia)
The aim of this study is to examine whether medieval charters could have been considered as a space for historiographical writing, for example by looking at the Norman conquest of Southern Italy and Sicily. A survey has been conducted in order to detect and identify any possible traces of remembering or commemorating the Norman Conquest in the charters written in the lands under the Hauteville’s authority. There are in fact very few such occurrences: the Hauteville conquerors did not mention the military or political events in their charters, and even their descendants, whose authority resulted from the success of this conquest, were not more voluble. The only cases of historiographical writing are actually those of revision, that is to say they are the result of documentary manipulation, such as forgery or interpolation found in Count Roger Ist’s diplomatic production. In general, not the rulers but the monasteries housing the charters in their archives were responsible for the re-writing. The instances of historical re-writing only expressed a vision of the conquest of Sicily as a religious expedition triggered to liberate the island from Islamic domination. Such a vision does not match Hauteville ideology, but may have been influenced by contemporary ideas from the crusading movement.